Phenotypic plasticity in floral scent in response to nutrient, but not water, availability in the perennial plant Arabis alpina. (12th July 2021) - Luizzi, Victoria J.; Friberg, Magne; Petrén, Hampus
Abstract: Floral scent is an important mediator of plant–pollinator interactions. Multiple recent studies report ample intraspecific scent variation among populations and individuals. Yet, few studies have estimated effects of phenotypic plasticity on floral scent in response to differing environmental factors. In this study, we investigated the effects of nutrient and water availability on floral scent in self‐compatible and self‐incompatible populations of the perennial herb Arabis alpina . We subjected greenhouse grown plants to different nutrient and water treatments in a crossed design, examined the effects on floral scent emission rate and composition, compared the level of plasticity to that of other plant traits, and conducted hand‐pollinations of nutrient‐limited individuals to test for a potential allocation cost of scent production. For both self‐compatible and self‐incompatible populations, the per‐flower scent emission rate was 1.2–4 times higher when nutrients were abundant, but this effect explained little variation in scent emission rate and was limited compared to plasticity in flower number. There was no effect of water treatment on scent emission. Additionally, neither treatment had an effect on the composition of the floral scent, and there was no detectable trade‐off between scent and seed production that would imply a cost of floral scent production. Overall, while per‐flower floral scent emission displayed limited phenotypic plasticity in response to nutrient conditions, the total amount of scent emitted by plants may increase more strongly at higher nutrient availabilities due to an increase in flower production. Therefore, our results suggest that fitness benefits due to increased scent emission rates under favourable nutrient conditions might depend on the extent to which floral scent serves as a long‐ or short‐distance pollinator attractant for the focal plant species. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.